2009
DOI: 10.1080/17477160802264507
|View full text |Cite
|
Sign up to set email alerts
|

Over and undernutrition in the children of Australian immigrants: Assessing the influence of birthplace of primary carer and English language use at home on the nutritional status of 4–5-year-olds

Abstract: There is a relationship between main language spoken at home and nutritional status in 4-5-year-old boys but not girls. The use of English language at home may be a protective factor for normal weight in young boys. After adjustment for socio-economic and demographics characteristics, there was a negligible relationship between overweight/obesity in children and their primary carer's country of birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…The prevalence of thinness in income rich countries has been shown to be higher in certain ethnic minority groups, such as Asian and Middle Eastern children [ 29 32 ]. This has prompted suggestions that the IOTF BMI cut-offs may overestimate thinness in these groups [ 32 ], although others have suggested that these elevated levels may be due to greater levels of disadvantage experienced by immigrant populations [ 31 ]. In the MCS, the prevalence of thinness was substantially higher in South Asian and ‘Other’ ethnic groups when compared to White children; and in the UK these groups tend to live in more disadvantaged circumstances [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of thinness in income rich countries has been shown to be higher in certain ethnic minority groups, such as Asian and Middle Eastern children [ 29 32 ]. This has prompted suggestions that the IOTF BMI cut-offs may overestimate thinness in these groups [ 32 ], although others have suggested that these elevated levels may be due to greater levels of disadvantage experienced by immigrant populations [ 31 ]. In the MCS, the prevalence of thinness was substantially higher in South Asian and ‘Other’ ethnic groups when compared to White children; and in the UK these groups tend to live in more disadvantaged circumstances [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is very limited information about the effect of acculturation on bone heath in men, but the use of the English language at home has been reported as a protective factor for normal weight in young boys in a nationally representative sample of children in Australia [39]. English language fluency was reported as predictor of hip fracture incidence in USA [15].…”
Section: Discussionmentioning
confidence: 99%
“…Combining fruit and vegetable intakes also reflects: (i) that diet is complex, comprising intakes of foods that correlate with one another (35) and do not operate alone (21) ; and (ii) dietary patterns may also predict the risk of disease better than individual foods ( P1 was asked whether the study child speaks a language other than English at home. Similar to Renzaho et al (36) , we grouped languages into two categories: 'English only' and 'Other language'…”
Section: Dietary Trajectory Outcomesmentioning
confidence: 99%